Aproximación al ‘minimismo’ latinoamericano (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2020)
This work proposes an approach to the construction of a definition of Latin American ‘minimism’. This expression, coined by the composer Graciela Paraskevaídis (1940- 2017), is taken as a starting point to verify certain characteristics that account for this category. In this sense, we propose to highlight traits such as austerity, deprivation and silence in compositional media as part of these researches by Latin American composers. Thus, we will illustrate those structural differences between Latin American ‘minimism’ and North American minimalism, as well as regarding European musical thought. Later, we will analyze in a repertoire selected for this occasion, elements that are associated with the premises by Coriún Aharonián (1940-2017) and Graciela Paraskevaídis, and that allow to exemplify the archetypal features of these musics.
Keywords: Graciela Paraskevaídis; Coriún Aharonián; art and society